Rhizosphere and Rhizoplane Mycoflora of Albizia lebbek (Linn.) - , Yasmeen; Ajaz, Shamim (Indian Forester, 1999)
Rhizosphere and rhizoplane mycoflora of Albizia lebbek was studied. In all 23 species of fungi belonging to 18 genera were isolated from both rhizosphere and rhizoplane. The frequency and number of fungi was more in rhizosphere as compared to rhizoplane.